Theatre, performance and affect through revolutionary times in Egypt - Khattab, Noha (AUC Knowledge Fountain, 2014)
Interactive street theatre is this significant genre of theatre that takes the stage to the audience. It is a genre that stages its performances beyond the walls of theatre houses, and finds its space within the everyday. This Thesis is an ethnographic study about interactive street theatre in Egypt post 2011.It explores how street theatre creates alternative spatiality and temporality that triggers possibilities of change through imagination. In this thesis I am focusing my analysis of two street theatre troupes who are particularly concerned with taking the stage to "marginalized" audience, and by this act they tend to create spaces for expression and imagination.